BETTER MOVERS AND THINKERS (BMT): AN INNOVATIVE APPROACH TO TEACHING PRIMARY SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2016)
Recent research has reignited interest into the physical and cognitive benefits of physical activity with some studies specifically highlighting beneficial aspects of activity on Executive Functioning  .  Executive Functioning (EF) is an umbrella term that describes the complex cognitive processes required to perform novel or difficult goal-directed tasks, including the ability to delay or inhibit responses, develop a plan of action sequences, and working memory.  Recent research has suggested plausible links between physical activity and the  enhancement of EF including; physiological influences such as greater cerebral blood flow; increased secretion of neurotrophins as a result of increasing levels of physical activity; psychological influences such as an increase in self-esteem and a desire to learn and be part of the school .  Other studies have identified that no decrease in academic performance has been observed despite a curtailing of time spent teaching academic subjects in favour of more time participating in PE  .  Aside from the cognitive gains that can be attributed to increasing time allocated to PE (and consequently being physically active), there is a well-established link between increasing levels of physical activity and the general health of children  .